Sex differences in the use of spatial cues in two avian brood parasites - Lois Milevicich, Jimena (2020)
Shiny and screaming cowbirds are avian interspecific brood parasites that locate and prospect host nests in daylight and return from one to several days later to lay an egg during the pre-dawn twilight. Thus, during nest location and prospecting, both location information and visual features are available, but the latter become less salient in the low-light conditions when the nests are visited for laying. This raises the question of how these different sources of information interact, and whether this reflects different behavioural specializations across sexes. Differences are expected, because in shiny cowbirds, females act alone, but in screaming cowbirds, both sexes make exploratory and laying nest visits together. We trained females and males of shiny and screaming cowbird to locate a food source signalled by both colour and position (cues associated), and evaluated performance after displacing the colour cue to make it misleading (cues dissociated). There were no sex or species differences in acquisition performance while the cues were associated. When the colour cue was relocated, individuals of both sexes and species located the food source making fewer visits to non-baited wells than expected by chance, indicating that they all retained the position as an informative cue. In this phase, however, shiny cowbird females, but not screaming, outperformed conspecific males, visiting fewer non-baited wells before finding the food location and making straighter paths in the search. These results are consistent with a greater reliance on spatial memory, as expected from the shiny cowbird female’s specialization on nest location behaviour.